Risk factors for the development of stifle injuries in canine agility athletes - Kieves, Nina R.; Shoben, Abigail; Markley, Arielle Pechette (Frontiers in Veterinary Science, 2024)
Objectives: Our aim was to determine risk factors for developing stifle injuries in canine agility athletes. We hypothesized that increased weight, increased frequency of competing, and greater number of runs/day would increase risk. Study Design: Internet based survey, n=4,197 Methods: Individuals with at least one dog who had competed in agility in the past three years were eligible. Injury history was defined as an injury to the stifle that kept the dog from participating in agility for >one week. Logistic regression models were used to estimate associations between variables of interest and injury history. Results: Handlers of 216 dogs reported a history of injury. The majority were cranial cruciate ligament (CCL) injury (101/216), and patella luxation (40/216). In the final model, five variables were independently associated with odds of stifle injury (in addition to age). Heavier dogs (adjusted for height), Border Collies, male dogs neutered <10 months, female dogs spayed before their first heat cycle, handlers aged 18-24, and teeter contact behavior were associated with increased risk. Conclusion: Heavier dogs were more likely to report injury, but there was no association with injury and increased number of competition days, or runs/day. The Border Collie breed was at the highest risk of injury. There was substantial risk for stifle injury with early spay/neuter. Additionally, a significant increase in risk of injury was reported for younger (18-24) vs. older handlers (65+). Athlete fitness level, conformation, and genetic predisposition to injury may play the most significant role in the development of injury.